Tipe Partisipasi Politik Masyarakat Suku Bugis Dalam Pemilihan Walikota Samarinda Tahun 2020 - Ahmad Dzaky; Adam Idris; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to determine the Types of Community Political Participation in the 2020 Samarinda Mayor Election. Using a descriptive method with a qualitative approach where data sources are obtained from observations and direct interviews in the field. To focus on his own research by looking at the opinions of Milbrath and Goel in Muslim (2018: 17) regarding the types of political participation, namely apathy, spectators, gladiators, critics. Based on the results of this research, apathy is seen from the Bugis Tribe Community who do not pay attention to or escape from the political situation, especially in the 2020 Samarinda Mayor Election. The Spectator is the Bugis Tribe Community who only participates in voting in the 2020 Samarinda Mayor Election. Gladiators are the Bugis Tribe Community in The City of Samarinda, which took full part in the 2020 Samarinda Mayoral Election Contestation, started from voting, nominating himself to becoming the organizing team and campaigner. The critic is the Bugis Tribe Society who has a type of pressure or Non-Conventional Participation.